Effect of an exercise-based intervention on physical function of frail elderly patients with acute coronary syndrome. (29th July 2021) - Ruescas-Nicolau, MA; Sastre-Arbona, C; Alabadi-Pardines, B; Gonzalez-Timoneda, A; Sanchis, J; Ruiz-Ros, V
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was supported by grants from CIBER CV, Madrid, Spain [grant number 16/11/00420] and Instituto de Salud Carlos III-FEDER, Madrid, Spain Background: Frail elderly patients with cardiovascular diseases are vulnerable and more likely to experience physical function decline. Of the interventions that have shown some efficacy in the management of frailty, exercise is the only treatment found to consistently improve physical function. Since the number of older persons with cardiac diseases is gradually increasing, understanding how therapeutic exercise might be successfully prescribed to prevent, or at least to reduce, the gradual decline in physical function in frail elderly patients, is a relevant issue. Purpose: To evaluate the effect of an exercise-based intervention on performance-based measures of physical function in frail elderly patients after acute coronary syndrome (ACS). Methods: A pretest-posttest design study was carried out. A cohort of elderly patients (age ≥70 years) hospitalized for ACS was included. Frailty was determined with the Fried scale. Participants received a three-month structured physiotherapy intervention that included, along with aerobic training, particular exercises for strength, flexibility, balance and coordination. Before and after the intervention, physical function was assessed with the Short Physical Performance Battery (SPPB). Results: Twenty three subjects (mean age 79 ± 3 years, 56.5 % men) participated. Of them, 13 were in a pre-frail status (Fried score = 1-2 points) while the other 10 were frail (Fried score >3 points). At baseline, the average Fried score was 2.35 ± 1.11. After the intervention, a significant difference was found for the SPPB total score (9.26 ± 2.73 vs 10.35 ± 1.87, p<.001). According to literature, this average 1.09-point increase in the SPPB score could be considered a clinically meaningful change. Also, there was a statistical significant increase after treatment in the partial scores of balance (3.3 ± 1.02 vs 3.83 ± 0.49 points, p=.005), gait speed (3.39 ± 1.11 vs 3.61 ± 0.78 m/s, p<.001) and leg strength (2.35 ± 1.19 vs 2.91 ± 1.1 points, p=.006). Conclusion: The proposed exercise-based physiotherapy intervention showed positive results in improving physical function in frail elderly patients with ACS. From a clinical viewpoint, measuring physical function and determining change over time are crucial since the deterioration of physical abilities are a strong predictor of future poor health outcomes, frailty, disability, and mortality in cardiovascular diseases.